30 lessons for loving : advice from the wisest Americans on love, relationships, and marriage - Pillemer, Karl A. (Hudson Street Press, 2015)
"Karl Pillemer asked hundreds of extraordinary men and women to share their hard-earned wisdom about love and what it takes to build a lasting, happy marriage. It is not only the largest study of its kind ever conducted, but also the most diverse, deliberately including people from varying religions, ethnic backgrounds, and income levels, gay and lesbian couples, unmarried couples in long-term relationships, and even individuals whose marriages were unhappy or ended in divorce"--